The Influence of the Technology Acceptance Model (TAM), E-System and the Role of the Account Representative on Taxpayer Compliance at West Makassar KPP - Kaliky, Faizah Salma; Rahim, Syamsuri; Wahyuni, Nur (Invoice : Jurnal Ilmu Akuntansi, 2024)
This research investigates the influence of the Technology Acceptance Model (TAM), E-System, and the Role of the Account Representative on taxpayer compliance at the West Makassar KPP. The study's population consists of all taxpayers registered at the West Makassar KPP, with a sample size of 88 taxpayers selected for analysis. To ensure the validity and reliability of the questionnaire results, thorough testing was conducted, including classical assumption tests such as normality, multicollinearity, and heteroscedasticity. The primary analytical method employed is multiple linear regression analysis. The findings reveal that the Technology Acceptance Model (TAM) exerts a significant positive impact on taxpayer compliance, indicating that when taxpayers perceive technology as beneficial and user-friendly, they are more likely to comply with tax regulations. Conversely, the E-System demonstrates a significant negative effect on taxpayer compliance, suggesting potential issues with its implementation or usability that hinder compliance. Furthermore, the role of the Account Representative is found to have a significant positive effect on taxpayer compliance, highlighting the importance of personal interaction and support in facilitating tax compliance. Overall, the study emphasizes the critical factors influencing taxpayer compliance, providing insights that could inform policy decisions and the development of strategies to enhance compliance at the West Makassar KPP. These findings are crucial for improving tax administration and ensuring greater adherence to tax obligations among registered taxpayers.